Immunogenicity after a Third COVID-19 mRNA Booster in Solid Cancer Patients Who Previously Received the Primary Heterologous CoronaVac/ChAdOx1 Vaccine - Sutima Luangdilok; Passakorn Wanchaijiraboon; Nussara Pakvisal; Thiti Susiriwatananont; Nicha Zungsontiporn; Virote Sriuranpong; Panot Sainamthip; Nungruthai Suntronwong; Preeyaporn Vichaiwattana; Nasamon Wanlapakorn; Yong Poovorawan; Nattaya Teeyapun; et al. (Vaccines, 2022)
No data regarding the efficacy of a third mRNA vaccine for solid cancer patients previously primed with the heterologous CoronoVac/ChAdOx1 vaccination implemented in Thailand during the shortage of vaccine supply are available. Forty-four cancer patients who previously received the heterologous CoronaVac-ChAdOx1 regimen were boosted with a third mRNA COVID vaccine, either BNT162b2 or mRNA-1273. Anti-RBD IgG was measured immediately before, two weeks after, and four weeks after the third dose. The antibody response was compared to 87 age- and gender-matched cancer patients who were primed with the homologous ChAdOx1/ChAdOx1 regimens. Post-third dose anti-RBD IgG levels significantly increased compared to pre-third dose levels. There was no statistical difference in post-third dose antibody titers or neutralization levels between these two primary series regimens. Treatment with chemotherapy was associated with a lower antibody response compared to endocrine therapy/biologics. Similar antibody levels were observed after a third booster with either BNT162b2 or mRNA-1273 following heterologous CoronaVac/ChAdOx1 vaccination. There was no statistical difference in the immune response following the third-dose vaccination between cancer patients and healthy individuals who received the same heterologous CoronaVac/ChAdOx1 vaccination. In conclusion, a similar degree of enhanced immunogenicity was observed after a third mRNA COVID-19 vaccination in solid cancer patients who previously received the heterologous CoronaVac/ChAdOx1 regimens.